If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 3(m + -2) = 6m + -12 Reorder the terms: 5m + 3(-2 + m) = 6m + -12 5m + (-2 * 3 + m * 3) = 6m + -12 5m + (-6 + 3m) = 6m + -12 Reorder the terms: -6 + 5m + 3m = 6m + -12 Combine like terms: 5m + 3m = 8m -6 + 8m = 6m + -12 Reorder the terms: -6 + 8m = -12 + 6m Solving -6 + 8m = -12 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. -6 + 8m + -6m = -12 + 6m + -6m Combine like terms: 8m + -6m = 2m -6 + 2m = -12 + 6m + -6m Combine like terms: 6m + -6m = 0 -6 + 2m = -12 + 0 -6 + 2m = -12 Add '6' to each side of the equation. -6 + 6 + 2m = -12 + 6 Combine like terms: -6 + 6 = 0 0 + 2m = -12 + 6 2m = -12 + 6 Combine like terms: -12 + 6 = -6 2m = -6 Divide each side by '2'. m = -3 Simplifying m = -3
| -2-7a=8-5a | | 5(2n+3)=8(6n+1)+4 | | -184=6-8(7-8n) | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 7m-(9-4m)=3(m-11) | | Y+3.9=11.8 | | -184=-8(7-8n) | | Y+3.9=11.8 | | 7m-(9-4m)=3(m-11) | | x^2+4x+2.2=0 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | -3d+-28=-40 | | -184=-8(7-8n) | | 16x-14=3(4x-5)+4x+1 | | 7m-(9-4m)=3(m-11) | | 7-2n=n+4 | | 8x+23=-5 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 8x+23=-5 | | 16x-14=3(4x-5)+4x+1 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | -184=-8(7-8n) | | 7+2(3c+1)=6c+9 | | 7-2n=n+4 | | 7+2(3c+1)=6c+9 | | 7m-(9-4m)=3(m-11) | | 8x+23=-5 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 2x-5=7x-105 | | 7+2(3c+1)=6c+9 | | 8x+4y+2z=16 | | -218=2r-8(6-4r) |